2021
DOI: 10.3389/fmolb.2021.633217
|View full text |Cite
|
Sign up to set email alerts
|

Local Electric Field Controls Fluorescence Quantum Yield of Red and Far-Red Fluorescent Proteins

Abstract: Genetically encoded probes with red-shifted absorption and fluorescence are highly desirable for imaging applications because they can report from deeper tissue layers with lower background and because they provide additional colors for multicolor imaging. Unfortunately, red and especially far-red fluorescent proteins have very low quantum yields, which undermines their other advantages. Elucidating the mechanism of nonradiative relaxation in red fluorescent proteins (RFPs) could help developing ones with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 88 publications
8
53
0
Order By: Relevance
“…The 1P and 2P excitation peaks for tdTomato are 554 and 1050 nm, while mScarlet is maximally excited at 569 nm and has a bimodal 2P excitation curve with peaks at 1065 and 1143 nm ( Fig. 1c ) 28, 29, 30, 31, 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…The 1P and 2P excitation peaks for tdTomato are 554 and 1050 nm, while mScarlet is maximally excited at 569 nm and has a bimodal 2P excitation curve with peaks at 1065 and 1143 nm ( Fig. 1c ) 28, 29, 30, 31, 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…Two factors mediate excited-state pathway selection: sterics, which acts upon large scale nuclear motion of two rings during isomerization, and electrostatics, which interacts with electronic redistribution during isomerization (or driving force). The electrostatic influence of the red fluorescent protein environment on the corresponding chromophore's FQY is also extensively discussed by a recent paper 42 , while our physical model treats electrostatics differently and explicitly incorporates the steric component (see Section S2 in Supporting Information). According to eq 5, FQY is a nonlinear function of Δ𝜈̅ , and thus the linear additivity of driving force does not translate to an additivity of FQY, as observed from the compensating hybrids (Figure 2D and Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Although increasing either of these two properties will proportionally increase brightness, it is not well understood how changes to the RFP structure can benecially impact their extinction coefficient, complicating the prediction of benecial mutations by rational design. On the other hand, it is known that the quantum yield of uorophores is directly related to their conformational exibility, [8][9][10] as motions can dissipate the absorbed energy as heat instead of as photons. In the case of uorescent proteins, it has been shown that twisting of the chromophore p-hydroxybenzylidene moiety via torsions in the methine bridge causes non-radiative decay.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of uorescent proteins, it has been shown that twisting of the chromophore p-hydroxybenzylidene moiety via torsions in the methine bridge causes non-radiative decay. 10,11 Therefore, it should be possible to enhance RFP brightness by designing mutations to restrict the conformational exibility of the phydroxybenzylidene moiety, resulting in higher quantum yield.…”
Section: Introductionmentioning
confidence: 99%